Double step method in lipid extraction from biomass Aurantiochytrium sp powder - Sulistiawati, Endah; Suhendra, Suhendra; Setyawan, Martomo; Mahsunah, Anis Herliyati (Institute of Advanced Engineering and Science, 2023)
Aurantiochytrium sp is a marine microalgae that is rich in lipids. Extraction of lipids from microalgae requires effort to select a suitable solvent and extraction method. This research used a double-step extraction method to study a mixture of n-hexane and methanol as a solvent. The variables studied were stirring time, the n-hexane to methanol (H/M) mixture ratio, and the solvent-to-biomass ratio (S/B). This research concluded that an optimum stirring time was 30 min, and a mixture of n-hexane and methanol solvents with a volume ratio of 1:1 is optimum. The optimum solvent-to-biomass ratio was S/B=20 mL/g dry microalgae. Under these conditions, the yield of oil was 83.88%. Double-step extraction can increase the yield by 10-40%.